Chinese Investment under China–Pakistan Economic Corridor: Implications on Banking Performance in Pakistan - Ullah, Sabeeh; Muhammad, Zia; Gul, Rauf (Public Finance Quarterly, 2021)
This study empirically examines the relationship of Chinese Foreign Direct Investment (CFDI) under the China-Pakistan Economic Corridor (CPEC) and commercial bank performance in Pakistan, thereby highlighting the un-explored area of the existing literature. For this purpose, a panel dataset over the period 2009 to 2020 of commercial banks was collected from the State Bank of Pakistan. We have employed various econometric techniques including random effect and System Generalized Method of Movement (Sys-GMM). To more accurately analyse the relationship between CFDI and bank performance, we also separately examined the pre-CPEC period 2009-2013, and the post-CPEC period 2014 to 2020. The results indicate a significant positive impact of Chinese FDI on the banking performance in Pakistan in full as well as in Pre-CPEC samples, while negatively significant with banking performance in Post-CPEC samples. For the control variables, we found some variations in signs and significance across the various bank performance measures and the three samples. This unique outcome of the study is very important for the policymakers of developing countries in general and Pakistan in particular.